Pendidikan Kesehatan dalam Pencegahan dan Penangan Diabetes Mellitus Melalui Penerapan Pola Hidup Sehat di Ruang Tulip RSUD Dr. Soehadi Prijonegoro Sragen - Yully Kurniawati; Salsabilla Az Zahra; Tyas Damastuti; Ida Nur Imamah (Jurnal Kemitraan Masyarakat, 2025)
Background: One of the factors that can trigger diabetes mellitus is a diet high in carbohydrates. Therefore, it is important to educate the community to adopt a healthy lifestyle in order to prevent various diseases, particularly diabetes mellitus. Objective: The objective of this health education activity on the prevention and management of diabetes mellitus through the implementation of a healthy lifestyle is to improve the knowledge of families of diabetes mellitus patients regarding prevention and management by applying healthy lifestyle practices. Methods: The activity was carried out for patients and their families using demonstration and discussion methods supported by leaflet media. Results: The counseling activity successfully increased respondents’ knowledge about the importance of preventing and managing diabetes mellitus through the implementation of a healthy lifestyle.Conclusion: Of the four respondents who attended the health education session on the prevention and management of diabetes mellitus through healthy lifestyle implementation, all participants demonstrated an understanding of the importance of adopting a healthy lifestyle for preventing and managing diabetes mellitus.